2017
DOI: 10.1111/jvp.12403
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous and transdermal fentanyl in alpacas

Abstract: The purpose of the study was to determine pharmacokinetics of fentanyl after intravenous (i.v.) and transdermal (t.d.) administration to six adult alpacas. Fentanyl was administered i.v. (2 μg/kg) or t.d. (nominal dose: 2 μg kg hr ). Plasma concentrations were determined using liquid chromatography-mass spectrometry. Heart rate and respiratory rate were assessed. Extrapolated, zero-time plasma fentanyl concentrations were 6.0 ng/ml (1.7-14.6 ng/ml) after i.v. administration, total plasma clearance was 1.10 L h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Other studies have evaluated the pharmacokinetics of intravenously fentanyl in horses (Maxwell et al., ), sheep (Ahern et al., ; Christou, Oliver, Rawlinson, & Walsh, ), goats (Carroll et al., ) and alpacas (Lovasz et al., ). The mean maximum concentration of 1.5 μg/L reported in our study was less than described by earlier reports in other large animal species when normalized with the input dose (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have evaluated the pharmacokinetics of intravenously fentanyl in horses (Maxwell et al., ), sheep (Ahern et al., ; Christou, Oliver, Rawlinson, & Walsh, ), goats (Carroll et al., ) and alpacas (Lovasz et al., ). The mean maximum concentration of 1.5 μg/L reported in our study was less than described by earlier reports in other large animal species when normalized with the input dose (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean maximum concentration of 1.5 μg/L reported in our study was less than described by earlier reports in other large animal species when normalized with the input dose (Table ). The estimated elimination half‐life of fentanyl in calves was apparently longer compared with other large animal species, such as sheep (3.1 hr), goats (1.2 hr) and alpacas (1.2 hr) (Lovasz et al., ). This must be interpreted with caution, however, as these values are compared to mature animals in these previous studies, and drug metabolism can be different between young and older animals of the same species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several drugs that can be administered via the transdermal route including fentanyl and more recently flunixin meglumine. A recent study evaluating the pharmacokinetics of transdermal (TD) fentanyl in alpacas found absorption of the drug to be variable (Lovasz et al, ). To date, there have been no studies evaluating flunixin meglumine in alpacas.…”
Section: Introductionmentioning
confidence: 99%